Mencermati Epistemologi Tasawuf - A. Khudori Soleh (Ulumuna, 2010)
Irfani, which has been developed and used in Sufism, is one of Islamic epistemologies well known in Islamic tradition in addition to bayani and burhani. Unlike bayani, which is based on scripture, and burhani, which is built on reason and logic, irfani builds on gnosis as its method of acquiring knowledge. The knowledge is transmitted directly from God and implanted in one’s heart without intermediary of logic and analysis. Such transmission occurs only through spiritual paces (maqâmât) and inner experience (hal). The irfani knowledge is classified into two categories: the unsaid and the said knowledge. The unsaid knowlege can only be exclusively understood by the person gaining it as extraordinary spiritual experience. Meanwhile, the said knowledge can be acquired through two ways: qiyas irfani and shattah. Unlike qiyas bayani that puts scripture as the origin and empirical experience as the branch, qiyas irfani places scripure as the branch of empirical spiritual experience